Vocabulary Self-Collection Strategy: Is It Effective to Improve Vocabulary Mastery Achievement on Senior High School Students? - Rizal Arisman (J-SHMIC : Journal of English for Academic, 2021)
The objective of this research was to find out whether there was a significant difference in vocabulary mastery between students who were taught using vocabulary self-collection strategy and those who were taught using a conventional method. This research used a quantitative approach with the experimental method of quasi-experimental design. There were 60 students involved as a sample of this research selected using the purposive cluster sampling technique. The instrument used was a test including pretest and posttest. Data were analyzed using Mann Whitney U test. The result indicated that the score of Asymp Sig. (2-tailed) was 0.001 which was fewer than α (0.05). It meant there was a significant difference in vocabulary mastery between students who were taught using vocabulary self-collection strategy and those who were taught using the conventional method. Furthermore, based on the result of the N-Gain test, it was found that the vocabulary self-collection strategy was more effective than the conventional method.